Review of Various Dimensions of Contrastive Studies by Bożena Cetnarowska, Marcin Kuczok and Marcin Zabawa (eds.), Katowice: Wydawnictwo Uniwersytetu Śląskiego, 2016 - Mokrosz, Ewelina; Zdziebko, Sławomir (LingBaW. Linguistics Beyond and Within, 2019)
The paper constitutes a review of a collection of articles entitled ‘Various Dimensions of Contrastive Studies’ published by Wydawnictwo Uniwersytetu Śląskiego in 2016 under the editorship of Bożena Cetnarowska, Marcin Kuczok and Marcin Zabawa. Each section of the review contains a critical evaluation of one paper found in the volume. We conclude that although the volume could benefit from more direct discussion pertaining to the methodology of contrastive studies, each of the articles constitutes a significant contribution to its particular domain and is worth-recommending to the reader who desires to keep track of the developments within different areas of the study of language.